Barriers of An Addict in Duncan Macmillan's Play People, Places and Things (2015) - Sari Megawati; An Fauzia Rozani Syafe’i (English Language and Literature, 2020)
This thesis is the analysis of a play which written by Duncan Macmillan entitled People, Places and Things (2015). It explores the issue of the barriers which experienced by an addict in getting well, escape from addiction and achieve the better life. It is reflected by the main character in the play. It is also intended to find out the contribution of fictional devices such as character, plot (conflict), and stage direction in revealing the issue of barriers of an addict. This analysis is related to the concept of life instinct which developed by Sigmund Freud that is supported by the text-based and context-based interpretation. The result of this analysis shows about the barriers that is experienced by the main character because the harmful substances she consumed such as internal barriers and external barriers.Key words: addict, barriers, external, internal